Pemasaran Digital untuk Produk Kerajinan Anyaman, Rajut, Manik-Manik di Cikarang Baru - Etty Zuliawati; Muhammad Iqbal Al Habsy; Shellometha Chinthya H; Azwa Aisa Fatqi (Lembaga Pengembangan Kinerja Dosen, 2024)
The Community Service program partners in this activity are Micro, Small and Medium Enterprises (MSMEs) engaged in crafts, such as weaving, knitting, and beaded jewelry, in the Cikarang Baru area. These MSMEs have been running their businesses for several years, but the marketing strategies applied are still conventional and therefore less effective. Therefore, it is important to provide training on the use of digital marketing so that the marketing system can be improved, expand market reach, and support increased product sales. In this activity, MSMEs receive training on the importance of digital marketing, as well as assistance in creating business accounts on digital platforms such as Google Business and Instagram, along with tutorials for optimal management. The outputs of this service include Google Business accounts, Instagram accounts, scientific articles published in national journals, and activity reports. The methods used in this service are lectures and practical tutorials in creating and managing accounts on digital media. The results of this activity indicate that digital marketing strategies need to be followed up with regular guidance so that they can function effectively and optimally in supporting marketing activities and increasing sales of MSME products.